Formação para o ensino da saúde na escola: o curso de educação física da Universidade Estadual Vale do Acaraú - Soares, Stela Lopes (2017)
In the current scenario of Brazilian education, dealing with health education in the school should be a relevant concern of the Physical Education teacher, since this professional is one of the responsible in the school field. In this way, it is understood health in the present time beyond the regular practice of physical activity considering the social determinants as decisive factor in the acquisition of health. There is still a gap in the curricular matrix in most of the undergraduate courses in Physical Education in the disciplines related to health education in the school. The objective of this study is to analyze the training offered in the undergraduate course in Physical Education of the UVA, for teaching health in school settings, in the municipality of Sobral, Ceará. To do so, it was used as an investigative question: how does the training, in the course of Degree in Physical Education of the UVA, for the teaching of health in school environments? Thus, 17 members of the collegiate of the Physical Education course of this institution participated in the study. Data collection was carried out in two phases: in the first, a documentary analysis of the Pedagogical Project of the Course; And, on the second, interviews with teachers were carried out. The main results indicate that there are no disciplines in the course curriculum for health and / or health education in the school and that the understanding of the majority of health research participants is limited. It is concluded that the Physical Education training of HEI researched for school health education is fragile, allowing only partial knowledge of health, since such understanding is broader and involves the acquisition of several factors such as: housing, leisure, Culture, education and employment.